Integrin‐Linked Kinase Regulates Bone Formation by Controlling Cytoskeletal Organization and Modulating BMP and Wnt Signaling in Osteoprogenitors. (30th June 2017) - Dejaeger, Marian; Böhm, Anna‐Marei; Dirckx, Naomi; Devriese, Joke; Nefyodova, Elena; Cardoen, Ruben; St‐Arnaud, René; Tournoy, Jos; Luyten, Frank P; Maes, Christa
ABSTRACT: Cell‐matrix interactions constitute a fundamental aspect of skeletal cell biology and play essential roles in bone homeostasis. These interactions are primarily mediated by transmembrane integrin receptors, which mediate cell adhesion and transduce signals from the extracellular matrix to intracellular responses via various downstream effectors, including integrin‐linked kinase (ILK). ILK functions as adaptor protein at focal adhesion sites, linking integrins to the actin cytoskeleton, and has been reported to act as a kinase phosphorylating signaling molecules such as GSK‐3β and Akt. Thereby, ILK plays important roles in cellular attachment, motility, proliferation and survival. To assess the in vivo role of ILK signaling in osteoprogenitors and the osteoblast lineage cells descending thereof, we generated conditional knockout mice using the Osx‐Cre:GFP driver strain. Mice lacking functional ILK in osterix‐expressing cells and their derivatives showed no apparent developmental or growth phenotype, but by 5 weeks of age they displayed a significantly reduced trabecular bone mass, which persisted into adulthood in male mice. Histomorphometry and serum analysis indicated no alterations in osteoclast formation and activity, but provided evidence that osteoblast function was impaired, resulting in reduced bone mineralization and increased accumulation of unmineralized osteoid. In vitro analyses further substantiated that absence of ILK in osteogenic cells was associated with compromised collagen matrix production and mineralization. Mechanistically, we found evidence for both impaired cytoskeletal functioning and reduced signal transduction in osteoblasts lacking ILK. Indeed, loss of ILK in primary osteogenic cells impaired F‐actin organization, cellular adhesion, spreading, and migration, indicative of defective coupling of cell‐matrix interactions to the cytoskeleton. In addition, BMP/Smad and Wnt/β‐catenin signaling was reduced in the absence of ILK. Taken together, these data demonstrate the importance of integrin‐mediated cell‐matrix interactions and ILK signaling in osteoprogenitors in the control of osteoblast functioning during juvenile bone mass acquisition and adult bone remodeling and homeostasis. © 2017 American Society for Bone and Mineral Research.